2007
DOI: 10.1093/hmg/ddm209
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and evolution of the novel gene family FAM90A in primates originated by multiple duplication and rearrangement events

Abstract: Genomic plasticity of human chromosome 8p23.1 region is highly influenced by two groups of complex segmental duplications (SDs), termed REPD and REPP, that mediate different kinds of rearrangements. Part of the difficulty to explain the wide range of phenotypes associated with 8p23.1 rearrangements is that REPP and REPD are not yet well characterized, probably due to their polymorphic status. Here, we describe a novel primate-specific gene family, named FAM90A (family with sequence similarity 90), found within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 59 publications
(52 reference statements)
0
17
0
Order By: Relevance
“…Given the evidence for recurrent inversion between the proximal and distal ␤-defensin loci discussed above, 1 simple mechanism for the creation of diversity in the placement of ␤-defensin repeats would be for frequent flipping of this sequence between different inversion states to sometimes include, and sometimes exclude, ␤-defensin repeats at each location. Although the copy-variable ␤-defensins have generally been treated as outside the inverted segment (28,29), it is evident that at least at the distal locus they are located between complex nested series of repeat sequences (REPD) (17,26,29,30), of which different elements may sponsor a variety of exchanges, including recombination between inverted repeats at REPP to mediate a change in inversion status. Despite the dynamic nature of the defensin repeats, it is clear that there are few if any repeats of variant gene composition; measurements of copy number within the defensin CNV have shown that the copy numbers of all genes in the repeat vary coordinately (18,21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the evidence for recurrent inversion between the proximal and distal ␤-defensin loci discussed above, 1 simple mechanism for the creation of diversity in the placement of ␤-defensin repeats would be for frequent flipping of this sequence between different inversion states to sometimes include, and sometimes exclude, ␤-defensin repeats at each location. Although the copy-variable ␤-defensins have generally been treated as outside the inverted segment (28,29), it is evident that at least at the distal locus they are located between complex nested series of repeat sequences (REPD) (17,26,29,30), of which different elements may sponsor a variety of exchanges, including recombination between inverted repeats at REPP to mediate a change in inversion status. Despite the dynamic nature of the defensin repeats, it is clear that there are few if any repeats of variant gene composition; measurements of copy number within the defensin CNV have shown that the copy numbers of all genes in the repeat vary coordinately (18,21).…”
Section: Discussionmentioning
confidence: 99%
“…1). REPP and REPD contain not only olfactory receptor gene repeats but also complex and polymorphic clusters of FAM90A genes (28). Approximately onequarter of Europeans and one-third of Japanese are heterozygous for this inversion; in these heterozygotes unequal recombination can lead to the formation of the pathological rearrangement inv dup(8p) or its reciprocal product, ϩder (8) (26,29).…”
mentioning
confidence: 99%
“…FAM90A1, the fourth most significantly mutated gene among B-cell lymphomas (16%) belongs to a gene family with 25 members in the human genome, several resulting from a primate-specific gene duplication (Bosch et al 2007). Dogs have four paralogs, of which only one is recurrently mutated in B-cell lymphoma.…”
Section: B-cell Lymphoma Defining Pathways Point To the Importance Ofmentioning
confidence: 99%
“…Among duplicons, we further identified ''core duplicons'' as the most abundant (top 10% of repeat-graph indices) duplicons among groups of intrachromosomal duplication blocks within a given chromosome ( Jin et al 2004;Jiang et al 2007). Core duplicons are associated with the emergence of new genes, dramatic gene-expression differences, and structural variation ( Johnson et al 2001;Paulding et al 2003;Ciccarelli et al 2005;Vandepoele et al 2005Vandepoele et al , 2009Popesco et al 2006;Bosch et al 2007;Jiang et al 2007). Due to the genomic complexity of their loci, the extensive copy number variation between and within species, and the lack of clear orthologs in model organisms of genes embedded in core duplicons, functional and genetic analyses of these genes have been particularly challenging.…”
mentioning
confidence: 99%